GPS: Guide to Personal Success Guide Manual 2013 - Kansas State University, K-State First (Kansas State University. K-State First., 2012)
This a guide for the faculty, staff, and alumni who serve as mentors to first-year students at Kansas State University. It highlights important expectations about the program and gives detailed advice on how to connect and communicate with students. It also offers examples on activities that mentors/mentees can participate in year-to-year.
Keywords: Mentoring; Program goals; Guide; Conversation Starters; Student Success; Brochures